The effect of stitching parameters on the puncture resistance properties of high strength fabric system / Suraya Ahmad Suhaimi - Suhaimi, Suraya Ahmad (2015)
The effect of stitching parameters on the puncture resistance properties of high strength fabric system was investigated. There are three objectives in this study; to investigate the effect of stitching patterns on the puncture resistance properties of the high strength fabric system, to investigate the effect of stitch density on the puncture resistance properties of the high strength fabric system, and to suggest the mechanism of penetration of the high strength fabric system. Four types of stitching patterns used in this study;vertical, diagonal, square and diamond stitched patterns. The samples were stitched with the nylon thread in two types of stitch density; 4 stitch/em and 8 stitch/em. The puncture resistance test was conducted and the conical shape probe was used in the test. The probe moved downward at 100 mrnlmin and stopped automatically when the maximum puncture load achieved. The results showed that diagonal, vertical and unstitch patterns gave much highest puncture resistance performance. Fabrics that were stitched with high stitch density offer higher puncture load value from 2-layer to 4-layer. There is a possibility of fabric slippage on the 5-layer and 6-layer fabric because the fabric samples became thicker and the clamping gap increased. The shape of the probe also contributed to the mechanism of penetration. The conical probe was able to push aside the principal yams. The sharp tip of the conical probe stretched the fibers and the stitch yams, break the fibers and stitch yarns, and then penetrate into the fabric. The local yam rupture was the fabric failure mode in this study. The puncture resistance of the high strength fabric system is dependent upon the number of fabric layers, types of stitching patterns, and the number of stitch density used to the fabric system